Efektivitas Bimbingan Kemandirian untuk Mewujudkan Ketahanan Ekonomi bagi Klien Pemasyarakatan Bapas Bukittinggi - Sikumbang, Indra; Elimartati; Yunarti, Sri (Federation of Indonesian Probation Officer, 2024)
This research was conducted to examine the effectiveness of the implementation of the independ- ence guidance program granted to correctional clients at Bukittinggi Probation and Parole Office (BAPAS Bukittinggi) toward the harmony of the client’s household. This research uses a qualitative descriptive approach where primary data is obtained by submitting questions to the correctional officers and clients of BAPAS Bukittinggi related to the implementation of independence guidance granted to clients. Based on this research, it was found that independent guidance for clients can be carried out and can be applied effectively so that clients have skills and economic independence from the work results obtained based on the skills they get from guiding. The implementation of independence guidance is not free from supporting and inhibiting factors in implementing the independence guidance granted to clients of BAPAS Bukittinggi, however, BAPAS Bukittinggi has strategies to overcome these inhibiting factors so that guidance can still be provided to clients. The efforts made to overcome obstacles to the implementation of independence guidance include: overcoming budget limitations, the im- plementation of guidance is carried out by providing independence guidance to the client by means of personal guidance by visiting the client's residence, to overcoming significant geographic locations, guidance is carried out by providing online guidance and carrying out guidance activities at the closest location to the client's own domicile; and to overcome limited facilities and infrastructure, the strategy implemented is optimizing existing equipment and infrastructure. [Penelitian ini dilakukan guna melihat efektivitas pelaksanaan bimbingan kemandirian yang diberikan kepada klien BAPAS Bukittinggi terhadap keharmonisan rumah tangga klien tersebut. Penelitian ini menggunakan pendekatan deskriptif kualitatif dimana data primer diperoleh melalui wawancara terhadap petugas dan klien BAPAS Bukittinggi berkaitan dengan substansi pelaksanaan bimbingan kemandirian. Berdasarkan penelitian ini, disimpulkan bahwa pembimbingan kemandirian dapat dilaksanakan dan diterapkan secara efektif sehingga klien memiliki keahlian dan kemandirian secara ekonomi melalui keterampilan yang mereka peroleh dari kegiatan bimbingan. Pelaksanaan pembimbingan kemandirian yang diberikan kepada klien BAPAS Bukittinggi tidak luput dari faktor pendukung dan penghambat. Akan tetapi, BAPAS Bukittinggi memiliki strategi untuk mengatasi fak- tor-faktor penghambat sehingga pembimbingan tetap dapat diberikan kepada klien. Adapun upaya- upaya yang dilakukan dalam mengatasi faktor penghambat pelaksanaan pembimbingan kemandirian antara lain: untuk mengatasi keterbatasan anggaran pelaksanaan bimbingan dilakukan dengan cara memberikan bimbingan kemandirian kepada Klien melalui bimbingan personal dengan mendatangi tempat tinggal klien; untuk mengatasi letak geografis yang luas maka pembimbingan dilakukan se- cara daring dan melakukan kegiatan bimbingan di lokasi terdekat dari domisili klien; adapun untuk mengatasi keterbatasan sarana dan prasarana, strategi yang diterapkan adalah mengoptimalkan sarana dan prasarana yang tersedia.]